2020
DOI: 10.1155/2020/7532703
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Mechanical Properties of Geopolymers Exposed to High Temperature: A Literature Review

Abstract: Geopolymers are prepared by alkali solution-activated natural minerals or industrial waste materials, which have been widely used as new sustainable building and construction materials for their excellent thermal and mechanical properties. The thermal and mechanical properties of geopolymers at high temperature have attracted great attention from many researchers. However, there are few systematic works concerning these two issues. Therefore, this work reviewed the thermal and mechanical behaviors of geopolyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 99 publications
2
43
0
2
Order By: Relevance
“…Najjar [ 33 ] found that the deterioration of concrete’s mechanical properties after sulfate corrosion was mainly due to reactions between SO 4 2 − and the aluminates (e.g., tricalcium aluminate, tetra-aluminate, and calcium monothioaluminate) of cement hydration products in concrete to produce ettringite (Aft) [ 34 , 35 , 36 ]. Additionally, sulfate corrosion tests revealed that the corrosion product Aft could be distributed throughout the ITZ and the internal concrete pores [ 37 ]. After Na 2 SO 4 eroded concrete under a dry-wet cycle, the evolution of Aft was studied via thermal difference-thermogravimetry [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Najjar [ 33 ] found that the deterioration of concrete’s mechanical properties after sulfate corrosion was mainly due to reactions between SO 4 2 − and the aluminates (e.g., tricalcium aluminate, tetra-aluminate, and calcium monothioaluminate) of cement hydration products in concrete to produce ettringite (Aft) [ 34 , 35 , 36 ]. Additionally, sulfate corrosion tests revealed that the corrosion product Aft could be distributed throughout the ITZ and the internal concrete pores [ 37 ]. After Na 2 SO 4 eroded concrete under a dry-wet cycle, the evolution of Aft was studied via thermal difference-thermogravimetry [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The researchers obtained thermal conductivity of the foamed geopolymers at 0.12 W/(m·K) in the case of a density of 0.36 kg/m 3 [ 30 ], and 0.10 W/(m·K) in the case of a density of 0.55 kg/m 3 [ 31 ]. The authors of paper [ 32 ] improved the thermal conductivity of geopolymer by simultaneously foaming it and introducing a hollow glass bead (HGB) into it. The products received in this way had a low density, and at the same time, a low value of the thermal conductivity coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…During the annealing of the samples above 1000 °C, a glass-like structure appeared on the surface of the material, and pore pressure grew gradually as a result of heat transfer and gas evaporation. When the vapor pressure exceeds the limit of the matrix, intensive thermal cracking and spalling, the pore structure collapsing, and further contraction could be observed [ 38 ].…”
Section: Resultsmentioning
confidence: 99%